(untitled) (Scientific journal of the Fergana State University, 2024)
This article briefly talks about the life and work of Khoja Abdulkholik Gijduvani. In addition to this, it is shown that Abdulkholik Ghijduwani’s “Vasiyatmona” for those in the khojagonian sect served as a kind of program and revealed the essence of the khojaganian sect for those who entered this sect. It is also mentioned that the works of this type are among the agiographic works and why they are included among the minor agiographic sources. Particular attention is paid to aspects of the “Vasiyatmona”, such as the repulsion from fanaticism and ignorance, and the promotion of science to enlightenment.